A retrospective analysis of the organization of foreign language training for personnel in the armed forces of NATO member states and Ukraine - Yaremchuk, Anastasia (Educological discourse, 2026)
This article presents a retrospective analysis of the organization of language training for personnel in the armed forces of NATO member states and Ukraine. The author emphasizes that English is currently the primary language used by NATO’s multinational armed forces to enhance their interoperability, and that organizing structured, professionally oriented foreign language training is a critical task in today’s reality. To this end, NATO member states established the International Language Coordination Bureau as a consultative and advisory body on language training issues. In 2003, the organization developed the STANAG 6001 language standard, which became an assessment tool and, at the same time, a foundation for training, promoting authenticity, functionality, and global comparability. The analysis conducted demonstrates that NATO countries have been able to create a unified system of foreign language training based on common standards within specialized military educational institutions. Currently, 48 countries use the STANAG 6001 criteria in their language systems. To this end, profession-oriented courses, training programs, and instructional materials have been developed; a standardized testing system has been implemented; and monitoring of learning outcomes has been ensured. At the same time, ensuring language training and standardization in Europe is crucial for the integrity of the European Union. Thus, the Common European Framework of Reference for Languages has been adopted in European Union countries for English, French, and German. For Ukraine, the inclusion of STANAG 6001 in military training programs, the training of instructors and test developers, and the development of assessment methodologies ensure that the personnel of the Armed Forces of Ukraine achieve internationally recognized communicative competence, for which significant resources are allocated; thus, language learning is one of the most important tasks of professional training for military personnel in NATO member states and in Ukraine.